Hydro-mechanical behaviour of soils during water-soil gushing in shield tunnels using MPM. (May 2022) - Xie, Xiao-Chuang; Ceccato, Francesca; Zhou, Ming-Liang; Zhang, Dong-Mei
Abstract: Water-soil gushing has become the main risk affecting the safety of shield tunnels in water-rich sandy layers. In this paper, a two-phase single-point material point method (MPM) is used to simulate the evolution of gushing in shield tunnels and the hydro-mechanical responses of the surrounding soils. The method is validated by well-documented experiments. The influence of gushing on the surrounding soil can be divided into three zones: flow zone, disturbed zone, and stationary zone. Based on the development laws of the flow zone, the gushing process can be divided into three stages: the initial developing stage, the expansive developing stage, and the stable developing stage. Parametric analysis is carried out to investigate the effect of the gushing location, the buried depth of the tunnel, and the soil parameters. The lower the gushing location, the smaller the development rate of the gushing, but the greater the variation in soil stress. The shallower the tunnel depth for the gushing, the smaller the impact on deep layers, but the greater the influence on ground settlement. Increasing the friction angle can effectively reduce the area and the development rate of the flow zone.